(untitled) (Journal of Science and Technology, 2016)
Carica papaya L. is grown in plantations and home gardens mostly in the tropical regions of the world. The plants can be classified into three primary sexes, namely, male, hermaphrodite or bisexual and female. Pollination is by wind and Insects. Propagation is mainly by seed. Apart from being cultivated for the fruits as a source of food, Carina papaya is also grown for its latex which serves as a rich source of papain used commercially in the cosmetic, textile, food and drug industries. A number of pharmacologically active constituents have been isolated from Carte panava. Different pans of Cara papaya are used by traditional healers for the treatment of various ailments.